Synergistic impact of diabetes and cognitive impairment on all-cause and cause-specific mortality in Chinese older adults: A prospective population-based cohort study - Li, Zhiqiang; Wang, Shengshu; Liu, Shaohua; Gong, Xinran; Wang, Yanding; Wu, Di; Yang, Meitao; Li, Rongrong; Li, Haowei; Li, Xuehang; Chen, Shimin; Jia, Ruizhong; et al. (Frontiers in Endocrinology, 2022)
Background: Diabetes mellitus(DM) or cognitive impairment(CI) is known to be strongly associated with mortality. DM commonly coexists with CI and proportionally increases with age. However, little is known about the combined effect of cognitive function and diabetes on mortality. This study aimed to evaluate the combined effects of DM and CI on all-cause and cause-specific mortality in Chinese older adults. Methods: This prospective population-based cohort study was based on the Beijing Elderly Comprehensive Health Cohort Study. A total of 4,499 old adults were included. Cox’s proportional hazard models were utilized to calculate the effect of DM and CI on all-cause, cardiovascular disease (CVD) mortality, and cancer mortality, and a multiplicative term was introduced to study a potential interaction between DM and CI on outcomes. Results: During a median follow-up of 6.8 years (ranging from 6.6 to 11.7years), 667 (14.8%) participants died from all causes, 292 from CVD, and 215 from cancer. In the fully-adjusted model, participants with coexisting DM and CI had the highest risk of all-cause mortality [hazard ratios(HRs),3.08; 95% confidence intervals (CIs),2.30,4.11], CVD mortality (HRs,3.85;95% CIs,2.60,5.71), compared with individuals who were normal cognition and non-DM. We also found a multiplicative interaction between DM and CI in respect to all-cause (HRs, 2.46; 95% CI, 1.87,3.22) and CVD mortality (HRs, 3.15 95% CI, 2.19,4.55). In the diabetic population, CI was associated with an increased risk of all-cause mortality(HRs,2.09; 95%CIs,1.51,2.89), CVD mortality(HRs, 3.16; 95%CIs,2.02,5.05) compared with the normal cognition group. Restricted cubic spline revealed a linear inverse association between MMSE score and all-cause, CVD mortality in the total sample and participants without diabetes. But a nearly reverse J association was observed between MMSE and mortality from all causes and CVD in the diabetes group. Conclusion: The findings highlighted that cognitive impairment concomitant with diabetes further increases the risk of mortality. In addition to strengthening routine screening of cognitive functioning in older adults with early-stage diabetes, more extensive assessing prognostic risks has high clinical value for developing comprehensive treatment plans.